Deteksi Kemurnian Air Zamzam Menggunakan Metode Spektrofotometri Fourier Transform Infrared (FTIR) dan Kemometrik (Detection of Zamzam Water Purity Using Fourier Transform Infrared (FTIR) Spectroscopy Technique and Chemometrics) - Kun Rasyida; Bambang Kuswandi; Nia Kristiningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Zamzam water is the holy water located in the city centre of Mecca. This water is believed to have lots of benefits so that it consumed by moslems around the world. In 2010, saudi authorities implement strict rules regarding export of zamzam water. The rules led to the increase sale of fake zamzam water globally. The determination of zamzam water purity was develoved using FTIR spectroscopy combined with multivariate statistical methods (chemometrics). Zamzam water sample simulation consist of pure zamzam water, mineral water, and a mixture of zamzam water with mineral water in the concentration range of 10%-100%. Analysis of data using PLS, LDA, SIMCA, and SVM were based on two sets of data, in the whole absorption (4000-700 cm-1) and the absorption 1800-700 cm-1. The classification model LDA of data on the whole spectrum without preliminary treatment is the best chemometric classification model with recognition capabilitiy and ability of prediction of 100%, respectively. FTIR spectroscopy and chemometric methods have been sucessfully applied to detect the purity of zamzam water samples of circulating in Jember. Keywords: zamzam water, FTIR spectroscopy, chemometrics, training set, test set.